2020
DOI: 10.1097/mej.0000000000000627
|View full text |Cite
|
Sign up to set email alerts
|

What happens in the shock room stays in the shock room? A time-based audio/video audit framework for trauma team performance analysis

Abstract: Introduction A precise tool for analysis of trauma team performance is missing. Objectives To create a framework for trauma team performance analysis and feedback. Methods An observational study in a level I trauma centre in Lithuania was performed from January 1 2017 to August 31 2017. Audio/video review process was used to evaluate technical and nontechnical performance of the trauma team. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 16 publications
1
21
0
Order By: Relevance
“…Some studies have reported a reduction in patient age during lockdown as well as an 8%−9.1% increase in male patients. [ 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 18 19 20 ] In the present study, these changes were not statistically significant, supporting the published data from other studies. [ 6 10 11 18 21 ] Another important observation during the COVID-19 pandemic was a significantly prolonged time for patients to be transferred to the hospital.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Some studies have reported a reduction in patient age during lockdown as well as an 8%−9.1% increase in male patients. [ 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 18 19 20 ] In the present study, these changes were not statistically significant, supporting the published data from other studies. [ 6 10 11 18 21 ] Another important observation during the COVID-19 pandemic was a significantly prolonged time for patients to be transferred to the hospital.…”
Section: Discussionsupporting
confidence: 87%
“…The characteristics of the TT have been described in our previous study. [ 14 ] We have analyzed all TT activations. TT activations for severely injured patients (Injury Severity Score [ISS] >15) were analyzed in a subgroup analysis.…”
Section: Methodsmentioning
confidence: 99%
“…These insights give the opportunity to evaluate and discuss the prevailing guidelines and adapt them where needed ( 8 , 11 ). Although more studies are needed to measure the effect of reevaluating guidelines, assessment of recordings of clinical care can emphasize the continuous need for reinforcement of adherence ( 7 , 10 , 12 ).…”
Section: Using Recordings For Assessing Quality Of Carementioning
confidence: 99%
“…Four studies analysed compliance with protocols such as advanced trauma life support (ATLS), and full personal protective equipment (PPE) usage [10,[17][18][19]. The remaining five studies analysed overall trauma resuscitation performance to identify errors and assess team performance [5,9,[20][21][22][23].…”
Section: Assessment Of Technical Skillsmentioning
confidence: 99%
“…These studies focussed on optimal team size for trauma resuscitation and found that closed-loop communication was the only factor which led to orders being completed more rapidly [8,25]. Trauma video review allowed for multiple aspects of communication and team dynamics to be assessed, which can be difficult in real time [21,26]. Santora et al [10], showed that resident leadership qualities including pre-briefing, clear and direct orders, and control of resuscitation were significantly improved over their study period with trauma video review.…”
Section: Assessment Of Non-technical Skillsmentioning
confidence: 99%